Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jcp.29981
|View full text |Cite
|
Sign up to set email alerts
|

The conditioned medium of human embryonic stem cell‐derived mesenchymal stem cells alleviates neurological deficits and improves synaptic recovery in experimental stroke

Abstract: The transplantation of mesenchymal stem cells (MSCs) is of main approaches in regenerative therapy for stroke. Due to the potential tumorigenicity and low survival rate of transplanted cells, focuses have been shifted from cell replacement to their paracrine effects. Therefore, stem cell-conditioned medium (CM) therapy has emerged as an alternative candidate. Here, we investigated the effect of CM derived from human embryonic MSCs on experimental ischemic stroke. Wistar rats underwent ischemic stroke by the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 57 publications
(93 reference statements)
1
24
0
Order By: Relevance
“…This suggests that either autologous or allogeneic MSCs exhibit the desired paracrine effects. In another study by Asgari Taei et al., ESC-derived CM of MSCs (ESC-MSC-CM) led to increased functional recovery, reduced infarction volume, and reduced mortality [ 86 ]. They identified upregulation of GAP-43, SYP, and p-CREB in ischemic areas as possible mediators for recovery [ 86 ].…”
Section: Future Treatments: Limiting Reperfusion Damage and Recovering From Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that either autologous or allogeneic MSCs exhibit the desired paracrine effects. In another study by Asgari Taei et al., ESC-derived CM of MSCs (ESC-MSC-CM) led to increased functional recovery, reduced infarction volume, and reduced mortality [ 86 ]. They identified upregulation of GAP-43, SYP, and p-CREB in ischemic areas as possible mediators for recovery [ 86 ].…”
Section: Future Treatments: Limiting Reperfusion Damage and Recovering From Ischemic Strokementioning
confidence: 99%
“…In another study by Asgari Taei et al., ESC-derived CM of MSCs (ESC-MSC-CM) led to increased functional recovery, reduced infarction volume, and reduced mortality [ 86 ]. They identified upregulation of GAP-43, SYP, and p-CREB in ischemic areas as possible mediators for recovery [ 86 ]. Other experiments have also attempted to isolate which cytokines are responsible for this recovery.…”
Section: Future Treatments: Limiting Reperfusion Damage and Recovering From Ischemic Strokementioning
confidence: 99%
“…At the preclinical level, transplantation of MSCs, especially BMSCs, improved functional recovery in MCAO model rats. MSC transplantation was shown to reduce the lesion volume ( Koh et al, 2008 ; Li et al, 2010 ; Shen et al, 2011 ), enhance sensorimotor ( Huang et al, 2013 ) and cognitive functions ( Lowrance et al, 2015 ), promote angiogenesis and neurogenesis ( Bao et al, 2011 ), modulate inflammatory and immune responses ( Ohtaki et al, 2008 ), and improve synaptic recovery ( Asgari Taei et al, 2021 ). Although some studies have shown no significant reduction of ischemic lesion volumes, the functional outcome nevertheless improved after the administration of MSCs; these discrepancies were suggested to be due to not recanalizing the middle cerebral artery ( Zacharek et al, 2010 ; Gutiérrez-Fernández et al, 2013 ).…”
Section: Mesenchymal Stem Cells (Mscs) In Ischemic Strokementioning
confidence: 99%
“…However, this approach has not yet been tested in humans. Most of the current studies were conducted in animal models ( Table 1; Brenneman et al, 2010;Chang et al, 2013;Kawabori et al, 2013;Cheng et al, 2015;Webb et al, 2018;Tian et al, 2019;Tobin et al, 2020;Asgari Taei et al, 2021). Further studies are needed to determine the best route for stem cell transplantation in treating stroke patients.…”
Section: Stem Cell Transplantationmentioning
confidence: 99%